Dual-phase MoS2 as a high-performance sodium-ion battery anode. Issue 4 (9th January 2020) - Wu, Junxiong; Liu, Jiapeng; Cui, Jiang; Yao, Shanshan; Ihsan-Ul-Haq, Muhammad; Mubarak, Nauman; Quattrocchi, Emanuele; Ciucci, Francesco; Kim, Jang-Kyo
Abstract : A dual-phase MoS2 with expanded interlayer distance is fabricated for sodium storage. The dual-phase MoS2 shows significantly improved electrical conductivity and enhanced Na + diffusivity compared to the common 2H-MoS2 . Abstract : The increasing cost and limited availability of lithium have prompted the development of high-performance sodium-ion batteries (SIBs) as a potential alternative to lithium-ion batteries. However, it has been a critical challenge to develop high-performance anode materials capable of storing and transporting Na + efficiently. Amongst the various options, MoS2 has significant advantages including low cost, and a high theoretical capacity of ∼670 mA h g −1 . Nevertheless, MoS2 has several issues: its electronic conductivity is low and its structure deteriorates rapidly during charge/discharge cycles, leading to a poor electrochemical performance. Here, a dual-phase MoS2 (DP-MoS2 ) is synthesized by combining two distinct 1T (trigonal) and 2H (hexagonal) phases to solve these challenges. Compared to the conventional 2H-MoS2 counterpart, the DP-MoS2 phase material presents a highly reversible Na + intercalation/extraction process aided by expanded interlayer spacing along with much higher electronic conductivity and Na ion affinity. Consequently, the DP-MoS2 electrode delivers a high cyclic stability with a reversible capacity of 300 mA h g −1 after 200 cycles at 0.5 A g −1 and an excellent rate capability of ∼220 mA h g −1 at 2 A g −1 . The SIBs assembled with DP-MoS2 and Na3 V2 (PO4 )3 as the negative and positive electrodes, respectively, have a specific capacity of 210 mA h g −1 (based on the mass of DP-MoS2 ) at 0.5 A g −1 . This performance demonstrates that DP-MoS2 has a significant potential in commercial devices. This work offers a new approach to develop metal chalcogenides for electrochemical energy storage applications.